Assessment of spatial neglect among stroke survivors: a neuropsychological study - Alqahtani, Mohammed M. J. (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2015)
Introduction : Spatial neglect is a common consequence of stroke and an independent predictor of rehabilitation outcomes. Therefore, assessing spatial neglect is very important. The aim of the study was to assess the clinical usefulness of a test battery for the detection of spatial neglect in stroke patients with an inversed reading/writing spatial frame compared to Latin languages on the basis of an Arabic population. Material and methods : There were 264 stroke survivors admitted to King Fahad Medical City-Rehab Hospital (KFMC-RH), 165 of whom met the inclusion criteria for this study. They were given a battery of neuropsychological tests, including a preliminary assessment of spatial neglect. Results : The percentage of stroke patients who showed spatial neglect ranged from about 18% to 41%, depending on the tools used. The high prevalence of spatial neglect was detected by the bell cancellation test, while the 5 cm line bisection test showed the lowest prevalence of spatial neglect. The entire neuropsychology battery detected more symptoms of spatial neglect than did any single test, as approximately 54% of patients in this study demonstrated spatial neglect symptoms on at least one test. Conclusions : The results encourage rehabilitation professionals in Saudi Arabia to use this neuropsychological battery to detect neglect syndrome in stroke survivors with a writing/reading right-to-left-oriented spatial frame. Increased awareness of the potential mediating role of spatial neglect in post-stroke symptoms will facilitate effective diagnoses and better rehabilitation intervention, resulting in better outcomes.